Caracterização parcial do gene 16S rRNA de isolados do solo e seus potenciais na solubilização de fostato e influência no crescimento de soja (Glycine max) e milho (Zea mays) - Almeida, Wallynson Eduardo Silva [UNESP] (2017)
The microorganisms have an active participation in the transformations of the phosphorus (P) in the soil, influencing its availability to the plants and their flow in nature. The transformations result from decomposition and mineralization of organic compounds, immobilization in the microbiomass and solubilization of inorganic forms of minerals. The base of this study was to evaluate 10 bacterial isolates, aiming to characterize them as: growth pattern in Tryptone Yeast (TY) medium (growth pattern in NBRIP medium; solubilization of calcium hydroxide phosphate Ca5OH (PO4) 3), pH variation in the different media, partial sequencing of the 16S rRNA gene, and growth influence in the greenhouse for soybean (Glycine max) and maize (Zea mays) crops.The best solubilizers In 120 h of culture were the isolates LGA-11-V0522, 33.81 mg / ml, Chromotacterium Violaceum, LGA13-V20F, 32.65 mg / ml, Arthrobacter echigonensis, LGA1-V4-V20J, 32.19 mg / ml , Arthrobacter echigonensis, and LGA05- V0513, 30.96 mg / ml, Bacilus Cereus, and LGA13-V20F, 22.67 cm. In the greenhouse, LGA09-V20L, 22.0 cm, Bacillus thuringiensis, LGA07-V0508, 21.25 cm, Bacillus thuringiensis, and LGA12-V05D 19.25, Bacillus thuringiensis.